ORGANISASI KERJA SAMA ISLAM (OKI) SEBAGAI ENTITAS KOSMOPOLITAN DEMOKRATIK: ANALISIS DINAMIKA INTERNAL DAN TANTANGAN STRUKTURAL - Sabda Ningsih (Indonesian Journal of International Relations, 2025)
This study analyzes the internal dynamics and structural challenges faced by the Organization of Islamic Cooperation (OIC) in realizing a democratic cosmopolitan entity, addressing a literature gap regarding its democratic practices. Employing the concept of democratic cosmopolitanism with indicators of inter-state equality, cultural hybridity, and individual Human Rights (HR) implementation, this qualitative descriptive-analytical research utilizes document analysis. Findings reveal that the OIC grapples with inter-state inequality due to political hegemony, and while efforts for cultural hybridity exist, internal sectarian diversity remains largely unintegrated. Individual HR implementation is selective, with political participation often restricted despite some progress in social and cultural HR. In conclusion, the OIC demonstrates selectivity in adopting democratic elements, showing cautious openness in economic democracy and certain social/cultural HR issues; however, dominant internal political dynamics and structural challenges, particularly hegemony and unresolved cultural issues, position the OIC far from being a fully democratic cosmopolitan entity.